Sikap Dan Perilaku Anak Mengenai Kebiasaan Menyikat Gigi Sebagai Tindakan Pencegahan Karies - Abubakar, Syamsuddin; Angki, Johnny; Musdalifa, Rindi (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
Oral health problems are difficulties that require a holistic approach because they have far-reaching effects on a person who has dental disease, including their physical, emotional, and social well-being. This study aims to determine the effect of children's attitudes and behavior on the habit of brushing teeth as a preventive measure for caries in elementary school children at SD Inpres Unggulan BTN Pemda. The method used in this research is descriptive quantitative with a cross-sectional approach. The population of this study were all 412 students of SD Inpres Unggulan BTN Pemda. The sampling technique in this study used Stratified Random Sampling technique with a total sample of 6th grade students of SD Inpres Unggulan BTN Pemda, namely 68 people. Data collection using instruments in the form of questionnaires and diagnostic tools. Data analysis techniques used in this study are editing, data coding, processing, and cleaning using Univariate analysis and Bivariate chi-square test. The results showed that there was a significant relationship between the attitude and behavior of tooth brushing habits with the caries condition of BTN Pemda's superior SD Inpres students.